UPAYA PENCEGAHAN DAN DETEKSI DINI KANKER PAYUDARA DENGAN PERIKSA PAYUDARA SENDIRI (SADARI) DI DESA MALAKASARI BALEENDAH - Dila Nur Fadillah; Miqdad Syadid Qutbh Alfani; Muhammad Yusril Yusup; Rasti Mutiara Audia; Yopan Sopian; Iis Dewi Fitriani (Jurnal Pengabdian Kepada Masyarakat, 2023)
Breast cancer is a malignant tumor that is formed from breast cells that grow and develop uncontrollably so that they can spread between tissues or organs near the breast or to other parts of the body. Female gender is the strongest breast cancer risk factor, certain factors increase the risk of breast cancer including increasing age, obesity, harmful alcohol use, family history of breast cancer, history of radiation exposure, reproductive history (such as age at the start of menstrual periods and gestational age first), tobacco use and postmenopausal hormone therapy. This research aims to reduce the death rate due to breast cancer by providing public health education to increase awareness among women regarding the signs and symptoms of breast cancer. The method used in this research is the method of socialization, lectures, practice using media in the form of brochures. Counseling material includes understanding breast cancer, signs and symptoms, risk factors for breast cancer, the importance of BSE and the steps involved.